TANTANGAN PENGGUNAAN AI BAGI PENDIDIKAN ISLAM - Yona Riska Amelia (Yayasan Baitul Hikmah al-Zain, 2026)
The integration of Artificial Intelligence (AI) into education has introduced significant transformations in how teaching, learning, and assessment processes are conducted. AI offers various benefits, including personalized learning paths, intelligent tutoring systems, and administrative efficiency. However, its implementation also presents a range of critical challenges that must be addressed to ensure its effective and ethical use in educational settings. One major concern is data privacy and the ethical handling of student information, especially as AI systems rely heavily on data collection and analysis. Additionally, algorithmic bias can lead to unfair treatment or reinforce existing educational inequalities if not properly managed. The lack of digital infrastructure and technological literacy in some regions may widen the digital divide, limiting access to AI-enhanced education for marginalized communities. Furthermore, over-reliance on AI tools could reduce meaningful human interaction and the role of educators in shaping character, values, and social-emotional learning. The rapid evolution of AI technologies also demands continuous updates in teacher training and curriculum design. Addressing these challenges requires collaboration between educators, technologists, and policymakers to develop clear ethical guidelines, promote equitable access, and ensure that AI serves as a supportive tool rather than a replacement. Ultimately, the goal is to leverage AI to enhance, not hinder, the human-centered nature of education.